2022
DOI: 10.1093/imrn/rnab355
|View full text |Cite
|
Sign up to set email alerts
|

Valuations and the Hopf Monoid of Generalized Permutahedra

Abstract: The goal of this paper is to show that valuation theory and Hopf theory are compatible on the class of generalized permutahedra. We prove that the Hopf structure $\textbf {GP}^+$ on these polyhedra descends, modulo the inclusion-exclusion relations, to an indicator Hopf monoid $\mathbb {I}(\textbf {GP}^+)$ of generalized permutahedra that is isomorphic to the Hopf monoid of weighted ordered set partitions. This quotient Hopf monoid $\mathbb {I}(\textbf {GP}^+)$ is cofree. It is the terminal object in the categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…Many invariants of matroids satisfy valuativity, including the Tutte polynomial and its specializations [AFR10,DF10]. For a more comprehensive list see [AS20], and see [ESS21] for a study of valuativity for Coxeter matroids. We show that a wide range of classes associated to the tautological K-classes of matroids are also valuative.…”
Section: Base Polytope Propertiesmentioning
confidence: 99%
“…Many invariants of matroids satisfy valuativity, including the Tutte polynomial and its specializations [AFR10,DF10]. For a more comprehensive list see [AS20], and see [ESS21] for a study of valuativity for Coxeter matroids. We show that a wide range of classes associated to the tautological K-classes of matroids are also valuative.…”
Section: Base Polytope Propertiesmentioning
confidence: 99%
“…What can be said about 0/1 extended generalized permutohedra with the same indicator complex (whether or not it is a matroid complex)? (15) Ardila and Sanchez [AS20] recently studied valuations of generalized permutohedra by passing to a quotient of GP `by inclusion/exclusion relations, as in Mc-Mullen's polytope algebra [McM89]. They showed that this quotient is isomorphic to a Hopf monoid of weighted ordered partitions.…”
Section: Proofmentioning
confidence: 99%
“…The Hopf algebra of matroids was introduced by Crapo and Schmitt [CS05a,CS05b,CS05c]. The corresponding Hopf monoid was described by Aguiar and Mahajan [AM10, §13.8.2] and has attracted recent interest; see, e.g., [San20,Sup20,AS20,Bas20]. There are many definitions of a matroid (see, e.g., [Oxl11, Section 1]), but for our purposes the most convenient definition is that a matroid is a simplicial complex Γ on vertex set I such that the induced subcomplex Γ|S " tσ P Γ : σ Ď Su is pure for every S Ď I (i.e., every facet of Γ|S has the same size).…”
Section: Introductionmentioning
confidence: 99%
“…Many matroid invariants, including the Tutte polynomial, the Kazhdan-Lusztig polynomial, the motivic zeta function, the Chern-Schwartz-MacPherson cycle, and the volume polynomial of the Chow ring, turn out to be valuative. See [AFR10,AS22,Ard22] for extensive lists and history of the study of valuative matroid invariants.…”
Section: Introductionmentioning
confidence: 99%